The Influence of Instagram Reels on English Vocabulary Acquisition among English Learners - Hasani, Muhammad Miftah; Zainuddin, Zainuddin; Hamdani, Beny (Universitas Nurul Jadid, 2025)
As one of the most popular social media platforms in the world, Instagram has evolved into a language learning tool through innovative features such as Instagram Reels. This study looks at several factors, such as the frequency of Instagram usage, the type of content consumed, and the way students use Instagram Reels to improve their English vocabulary. This study used a qualitative method by collecting Data through questionnaires provided to ten students from the English Education Study Program of Zainul Hasan University Genggong. The results of the study showed that the attractive and contextualized format of Instagram Reels significantly improved vocabulary acquisition. Instagram can be an effective educational tool, but it requires a planned strategy to maximize its benefits for students.